General introduction to non-clinical toxicity testing of pharmaceuticals - Weir, Andrea (Henry Stewart Talks, 2009)
Overview of the Food and Drug Administration (FDA), Role of the FDA in drug development, Overview of drug development from a non-clinical perspective, Non-clinical guidance documents and studies, Clinical trials, Using non-clinical data to support safe drug development, Comparison of humans to animal models, Correlation between clinical and non-clinical toxicities
Updated at 2016/12/28